A digitális élelmiszer-fogyasztó jellemzői = The characteristic of digital food consumer - Fehér, András (Közép-Európai Közlemények, 2018)
The age of Internet had an especially great impact on consumers who represent one of the main actors on the market. Digitalization and the way of healthy lifestlye are the most important trends in our modern age. My main objectives of the research the mapping of the domestic digital food consumer relevance about online food behaviour depending on information gathering and shopping. I used two main methods of marketing research in the article: the primary and secondary ones. I analysed about the characteristic of one of my main cluster (expert internet users) of my previous representative research (1000 samples about attitudes of Internet using) in details with an online representative survey with 305 samples. The main viewpoint was the online food consumer attitudes. The elements of the pattern were chosen with the help of a filtering question, so the members of the final pattern were the representatives of the Generation Y (between 20 and 35), who have already been a majority in an survey as well in comparison with other age groups. I examined two validated model’s and my own statements. The first one is the Internet Information Search Model (ISM) and the second one is Online Consumer Style Inventory (O-CSI). I used various types of descripting statistics, cross-chart analyses, then made a factor- and cluster analysis. I created five well-differentiated segments. I can say that in a small pattern (305 samples), but minding the relevant statistical methods in a maximum way, I could define groups of consumers who – based on their features and content – represent the information search and the offline and online shopping in a quite new way.